Serious Consequences of Malnutrition and Delirium in Frail Older Patients. Issue 2 (3rd April 2018) - Rosted, Elizabeth; Prokofieva, Tatiana; Sanders, Suzanne; Schultz, Martin
Abstract: Malnutrition is highly prevalent in geriatric patients and is associated with an increased risk of death. In addition, delirium is a common condition of the older hospitalized patients. As brain has a high nutritional requirement, malnutrition may play an important role in cognitive dysfunction including the development of delirium. This study investigated the association between delirium and malnutrition in frail older patients and the effects on adverse outcomes. It was found that 75% of the patients with delirium suffered from malnutrition indicating that malnutrition contributes to the development of delirium in older hospitalized patients. Patients suffering from both malnutrition and delirium had a four times higher mortality in one month follow-up, a seven times increased rate of discharge to nursing homes and three days more in hospital. All older patients should routinely be assessed for malnutrition and delirium at admission to hospital and to prevent the development of delirium a close follow-up must take place to ensure adequate nutrition.